The Kink Turn, a Key Architectural Element in RNA Structure. Issue 5 (27th February 2016) - Huang, Lin; Lilley, David M.J.
Abstract: Kink turns (k-turns) are widespread structural elements that introduce an axial bend into duplex RNA with an included angle of 50°. These mediate key tertiary interactions and bind specific proteins including members of the L7Ae family. The standard k-turn comprises a three-nucleotide bulge followed by G·A and A·G pairs. The RNA kinks by an association of the two minor grooves, stabilized by the formation of a number of key cross-strand hydrogen bonds mostly involving the adenine bases of the G·A and A·G pairs. The k-turns may be divided into two conformational classes, depending on the receptor for one of these hydrogen bonds. k-turns become folded by one of three different processes. Some, but not all, k-turns become folded in the presence of metal ions. Whether or not a given k-turn is folded under these conditions is determined by its sequence. We present a set of rules for the prediction of folding properties and the structure adopted on local sequence. Graphical Abstract: Highlights: k-turns are widespread elements that kink the axis of duplex RNA. k-turns mediate tertiary contacts and bind proteins. Both the folding process and the structure adopted depend on local RNA sequence. We have deduced a number of rules to associate sequence and folding. The rules have strong predictive power.